1998
DOI: 10.1074/jbc.273.3.1285
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Preferentially Induces the Rapid, Transient Expression of SOCS-3, a Novel Inhibitor of Cytokine Receptor Signaling

Abstract: Four members (SOCS-1, SOCS-2, SOCS-3, and CIS) of a family of cytokine-inducible, negative regulators of cytokine receptor signaling have recently been identified. To address whether any of these genes are induced in response to growth hormone (GH), serum-starved 3T3-F442A fibroblasts were incubated with GH for various time points, and the expression of the SOCS gene family was analyzed by Northern blotting. GH stimulated the rapid, transient induction of SOCS-3 mRNA, peaking 30 min after the initiation of GH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
218
2
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 291 publications
(244 citation statements)
references
References 14 publications
20
218
2
3
Order By: Relevance
“…Treatment with human rG-CSF resulted in a dramatic increase of SOCS-3 mRNA within 45 min. This rapid induction of SOCS-3 was similar to that observed with other cytokines (47)(48)(49) and this indicates that SOCS-3 is an immediate early gene induced by G-CSF to rapidly modulate G-CSFR-mediated signaling. The strong and rapid induction of SOCS-3 mRNA in myeloid cells by G-CSF reported in this study, together with the previously reported potent induction of SOCS-3 by G-CSF, GM-CSF, and IL-3 in bone marrow cells (22), is a strong indication for SOCS-3 being an important regulator of signal transduction in immune cells.…”
Section: Discussionsupporting
confidence: 82%
“…Treatment with human rG-CSF resulted in a dramatic increase of SOCS-3 mRNA within 45 min. This rapid induction of SOCS-3 was similar to that observed with other cytokines (47)(48)(49) and this indicates that SOCS-3 is an immediate early gene induced by G-CSF to rapidly modulate G-CSFR-mediated signaling. The strong and rapid induction of SOCS-3 mRNA in myeloid cells by G-CSF reported in this study, together with the previously reported potent induction of SOCS-3 by G-CSF, GM-CSF, and IL-3 in bone marrow cells (22), is a strong indication for SOCS-3 being an important regulator of signal transduction in immune cells.…”
Section: Discussionsupporting
confidence: 82%
“…GH was previously shown to induce strong transient expression of SOCS-3 in mouse liver [32]. Regulation of the GH intracellular signalization pathway occurs through a complex mechanism involving the coordinated action of various negative regulators, whose main targets apparently are JAKs and STATs phosphorylated by activated GHR [33].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, tumor necrosis factor ␣, a molecule thought to be involved in insulin resistance, has been shown independently to induce SOCS-3 (4) and to inhibit insulin-induced STAT5 activation (47). GH, a molecule known to lead to a state of insulin resistance (48), is also a recognized SOCS-3 inducer (49). Although this is still a matter of debate, leptin, an adipocyte-produced hormone, has been proposed to hamper insulin signaling (50,51) and is a recognized inducer of SOCS-3.…”
Section: Socs-3 As a Negative Regulator Of Insulin Signalingmentioning
confidence: 99%